Status Karyawan Sebagai Variabel Moderasi Antara Motivasi Dan Komitmen Organisasi Terhadap Organizational Citizenship Behaviour - Arief Adhy Kurniawan; Sutarmin Sutarmin (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
The problem in this research is their different behavior on different employee status, so it should be identified as a result of differences in the status of employees. The aims of this study was to determine the effect of motivation on organizational citizenship behavior (OCB) lecturer STMIK Amikom Purwokerto, motivational influence on organizational commitment lecturer STMIK Amikom Purwokerto, the influence of organizational commitment on organizational citizenship behavior (OCB) lecturer STMIK Amikom Purwokerto, and to know the status of employees in moderating the relationship between motivation and commitment to organizational citizenship behavior (OCB) lecturer STMIK Amikom Purwokerto. Samples were lecturers STMIK Amikom Purwokerto lecturer fixed and honorary. The analytical method used is linear regression analysis. The results showed positive effect on the motivation of organizational commitment, motivation positively influences on organizational citizenship behavior, organizational commitment positively affects organizational citizenship behavior and employee status does not moderate in the relationship between motivation and commitment to organizational citizenship behavior.